2019
DOI: 10.1007/s10336-019-01670-x
|View full text |Cite
|
Sign up to set email alerts
|

Great variability in nest lining size: support for thermoregulation but not for anti-predatory adaptation hypothesis

Abstract: Nest lining is a key component in nests of many bird species. Among ground-nesting birds with open nests, it usually consists of dry sticks and stalks creating a thermoregulatory insulating layer for the eggs. However, a bigger nest lining can attract predators and increase nest mortality. The factors influencing behavioural plasticity in birds facing the trade-off between nest lining thermoregulation and conspicuousness for predators have remained poorly understood. The Northern Lapwing Vanellus vanellus, a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Indeed, selection for larger nests could be constrained by predation risk, since many predators are diurnal and use vision to locate nests, and it is known that bigger nests, relative to body size, are more susceptible to predation (Møller, 1990;Martin and Li, 1992;Biancucci and Martin, 2010;Mouton and Martin, 2019). In fact, the pressure to construct small and inconspicuous nests may outweigh the pressure to produce a suitable nest microclimate (Møller, 1990;Crossman et al, 2011, but see Akresh et al, 2017Kubelka et al, 2019). These competing selection pressures can be particularly important for exposed, open cup nesters (Matysiokov and Remes, 2018).…”
Section: Nest Sizementioning
confidence: 99%
“…Indeed, selection for larger nests could be constrained by predation risk, since many predators are diurnal and use vision to locate nests, and it is known that bigger nests, relative to body size, are more susceptible to predation (Møller, 1990;Martin and Li, 1992;Biancucci and Martin, 2010;Mouton and Martin, 2019). In fact, the pressure to construct small and inconspicuous nests may outweigh the pressure to produce a suitable nest microclimate (Møller, 1990;Crossman et al, 2011, but see Akresh et al, 2017Kubelka et al, 2019). These competing selection pressures can be particularly important for exposed, open cup nesters (Matysiokov and Remes, 2018).…”
Section: Nest Sizementioning
confidence: 99%
“…The study area (~ 40 km 2 ) consisted of a mosaic of arable land, meadows, fishponds, forests, and human settlements. A population of ~ 100 pairs of the model species inhabited various habitats on arable land and meadows [ 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Maziarz (2019) demonstrated that the presence of nests of Marsh Tits Poecile palustris modifies the temperature and humidity of the cavities in trees in which the nest is built. Kubelka et al (2019) showed that nests of the Northern Lapwing Vanellus vanellus vary in the amount of lining material; those placed closer to small water pools experienced generally cooler microclimates and had bigger nest linings. Deeming et al (2020a) showed that, by selecting various materials whilst constructing a nest, birds can manipulate the thermal characteristics of the nest wall.…”
Section: Does the Nest Represent An Extended Phenotype And Can It Pla...mentioning
confidence: 99%